1981
DOI: 10.1093/infdis/143.3.396
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of a Cytopathic Paramyxovirus from Peripheral Blood Leukocytes in Subacute Sclerosing Panencephalitis

Abstract: An infectious, cytopathic paramyxovirus was rescued from the peripheral blood leukocytes of a patient with subacute sclerosing panencephalitis (SSPE) by cocultivation procedures. Cells infected with the virus (1) demonstrated polykaryocytosis, (2) contained cytoplasmic inclusion bodies of paramyxoviral nucleocapsids, (3) hemadsorbed monkey erythrocytes, and (4) reacted with fluorescein-conjugated antisera to measles virus. On the basis of these observations, the virus was initially believed to be measles-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…However, HPIV-1 and Sendai virus have been detected using PCR in tissue from the ofactory bulbs of mice (247,248). Animal PIV related to HPIV-2 have been found in patients with MS and subacute sclerosing panencephalitis (118,307). Two closely related paramyxoviruses (Hendra and Nipaha viruses) have been shown to cause severe encephalitis and death in children and adults (53,254,265).…”
Section: Clinical Syndromesmentioning
confidence: 99%
“…However, HPIV-1 and Sendai virus have been detected using PCR in tissue from the ofactory bulbs of mice (247,248). Animal PIV related to HPIV-2 have been found in patients with MS and subacute sclerosing panencephalitis (118,307). Two closely related paramyxoviruses (Hendra and Nipaha viruses) have been shown to cause severe encephalitis and death in children and adults (53,254,265).…”
Section: Clinical Syndromesmentioning
confidence: 99%
“…Simian virus 5 (SV5) was originally isolated from rhesus monkey kidney cell cultures (Hull et al, 1956) but has subsequently been isolated from tissues of other animals including humans (Hsiung, 1972;Robbins et al, 1981 ;Goswami et al, 1984) and dogs (Rosenberg et al, 1971 ;McCandlish et al, 1978). SV5 causes tracheo-bronchitis in dogs and is often associated with kennel cough (McCandlish et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of SV5 infections in monkeys is open to question (Hsiung, 1972) and it has been proposed that monkeys acquire infection via contact with humans after being brought into captivity (Tribe, 1966). On a number of occasions the isolation of SV5 from human tissue has been reported (Hsiung, 1972;Robbins et al, 1981), including on five separate occasions from the bone marrows of multiple sclerosis patients (Goswami et al, 1984;Mitchell et al, 1978). Limited seroepidemiological studies have indicated that a reasonably high proportion (20 to 40~) of people have antibodies that react with SV5 (Hsiung, 1972;Goswami et al, 1984).…”
Section: Introductionmentioning
confidence: 99%